Assessing Returns of IDX Sharia Growth Stocks: Applying The Fama-French Five-Factor Model For Portfolio Optimization - Yulandri, Elsa; Sobana , Dadang Husen; Asih, Vemy Suci; Nugraha; Waspada, Ikaputera; Sari, Maya (Global Review of Islamic Economics and Business, 2025)
This study examines the influence of the Fama-French five-factor model on the excess return of stocks listed in the Indonesia Stock Exchange Sharia Growth Index and offers recommendations for optimizing Sharia-compliant portfolios. The model includes five independent variables: overall market return, firm size (measured by the return difference between small and large firms), book-to-market value, profitability (difference between firms with strong and weak earnings), and investment strategy (difference between conservative and aggressive asset growth). The analysis uses quarterly data from 2022 to 2023 and selects 14 companies from the index based on data completeness and consistent listing. Multiple linear regression with the Ordinary Least Squares method reveals that only the market return and firm size factors have a significant effect on excess return, with firm size having the strongest impact. Meanwhile, the book-to-market value, profitability, and investment strategy factors do not show significant individual influence. However, when assessed collectively, all five factors explain 93.06 percent of the variation in excess return, indicating the model’s overall strength. The study is limited by its short time frame due to the recent launch of the index and its relatively small sample size. These findings suggest that Sharia-compliant investors should prioritize firm size and market trends in portfolio construction. Future research should incorporate longer time periods, broader index comparisons, and qualitative factors such as investor sentiment or environmental, social, and governance indicators to enhance understanding of return behavior in Islamic equity markets.